TRANSFORMASI AKUNTANSI SEKTOR PUBLIK INDONESIA: BASIS AKRUAL, DIGITALISASI, DAN PELAPORAN KEBERLANJUTAN - Agus Kurniawan; Zathu Restie Utami (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Public financial management reforms have transformed Indonesian public sector accounting from cash basis toward accrual basis while facing increasing demands for data-driven transparency and sustainability-related information. This article synthesizes current issues in public sector accounting by focusing on the interlinkages among accrual implementation quality, digital reporting, and sustainability reporting (including climate/SDGs disclosures). Using a structured literature review and policy document analysis (accounting standards, regulations, and audit summary reports) for 2015-2025, the synthesis indicates that: (1) accrual adoption is often strong in report preparation compliance but weaker in decision-usefulness and asset management; (2) improving audit opinions does not automatically translate into stronger performance accountability, calling for tighter integration of financial and performance reporting as well as audit follow-up; (3) digitalization through financial management information systems, open data, and standardized digital reporting (e.g., XBRL) can improve timeliness and comparability but raises data governance, data quality, and cybersecurity risks; and (4) emerging international public sector sustainability reporting standards provide an opportunity to broaden government reporting on climate risks and impacts. The article proposes an integrative framework and an implementation roadmap that balances standards, human-capital capability, data governance, and assurance. The main conclusion is that transformation should move from â€˜mere compliance’ toward â€˜decision-useful’ reporting that strengthens transparency and public accountability.